Alkyl gallates disrupt Trypanosoma brucei lipid droplets - Cynthia Mmalebna Amisigo; Gloria Amegatcher; Jack D. Sunter; Theresa Manful Gwira (PLoS ONE, 2026)
African trypanosomiasis is a deadly disease that affects humans and animals, with treatment hindered by drug toxicity and resistance, highlighting the need for alternative therapies. Alkyl gallates, which are plant-derived phenolipids used in the food, cosmetics, and pharmaceutical industries, have been shown to have potent anti-microbial activity; however, their mechanism of action is still unclear. This study investigated the effects of selected alkyl gallates on Trypanosoma brucei . The in vitro anti-trypanosomal and cytotoxicity of the alkyl gallates were determined using the alamarBlue assay. The effects of the alkyl gallates on lipid droplet dynamics were studied using BODIPY493/503 dye and an endogenously tagged lipid droplet kinase cell line which served as a protein marker of lipid droplets. In vitro treatment with octyl and lauryl gallates resulted in rapid cell death with low IC 50 of 0.7 µM and 0.04 µM respectively. Octyl gallate treatment significantly reduced lipid droplet number within 30 minutes and by 2 hours most cells lacked lipid droplets; however, lipid droplets rebounded once the drug pressure was removed. These results show that alkyl gallates rapidly disrupt lipid droplet homeostasis in Trypanosoma brucei . Thus, these gallates could serve as a useful cell biology tool to dissect lipid droplet biogenesis and function in trypanosomes.